Characteristics and modeling kinetics of oil palm frond petiole pyrolysis using thermogravimetric analyzer. Issue 1 (September 2021) - Prasetiyo, A; Sukarni, S; Wibowo, A A; Permanasari, A A; Puspitasari, P
Abstract: As one of the largest palm oil-producing countries globally, Indonesia produces abundant oil palm biomass; indeed, it brings large oil palm frond petiole (OPFP). OPFP is one of the oil palm biomass that can be converted into an energy source. This research focuses on analyzing thermal decomposition characteristics and pyrolysis kinetics of OPFP using thermogravimetric analysis (TGA). The results showed that the thermal decomposition of pyrolysis was divided into three steps, including the evaporation stage of moisture content, the releasing of volatile compounds and organic matter, and the final stage of lignin and tar decomposition. Both the activation energy and the pre-exponential factors were analyzed with the Coats-Redfern method in step II active pyrolysis zone are 80.56 kJ/mol and 7.21/min, respectively, as shown in the Chemical Reaction Order F1.5 model with the accuracy of a correlation coefficient of 0.99. These results provided the fundamental data useful for properly designing the reactor system for industrial purposes.